Evolving Neural Network for Kernel Principal Component Analysis - Turuta, O.; Deineko, A. O.; Perova, I.; Kutsenko, Y.; Shalamov, M. (IJCSMC, 2015)
In the paper kernel evolving neural network and its learning algorithm are investigated. The proposed system solves the problem of finding the eigenvectors and the corresponding principal components in on-line mode in an environment where hidden in the experimental data interdependencies are nonlinear and can change throw time.
Keywords: Principal component analysis (PCA); Dynamic Data Mining; Data Stream Mining; radial-basis neural networks (RBFN); kernel evolving neural network; dynamic data mining (DDM); data streams mining (DSM)